Association between Plasma Uric Acid Level and Mortality Rate in Children with Sepsis and Acute Kidney Injury - Sadeghi Bojd , Simin; Soleimani, Gholamreza; Yaghoubi, Saeedeh; Sarhadi, Saeedeh; Khazaei, Nooshin; Nikbakht, Javad (Urology Journal, 2026)
Purpose: Acute kidney injury (AKI) is a common condition in hospitalized patients that can have a significant impact on outcomes, including an increase in overall complications and mortality rates. Criteria such as serum creatinine level, urinary output, and scoring systems such as KDIGO in acute conditions do not have acceptable specificity and sensitivity to evaluate kidney function. Therefore, this study was conducted to determine the relationship between plasma uric acid level and mortality rate in patients with sepsis and acute kidney failure. Materials and Methods: In this descriptive-analytical (cross-sectional) study, 52 children aged from one month to 15 years with sepsis (based on qSOFA criteria) and acute kidney failure (based on serum creatinine level) admitted to the PICU of Ali Bin Abi Taleb Hospital from October 1401 to October 1402 were included and studied by the census method. Within 48 hours after admission to the ICU, blood samples were collected to check serum uric acid levels, electrolytes, albumin, complete blood count (CBC), kidney function tests, arterial blood gases, and chest x-rays. All patients were followed up until discharge or death due to progression of kidney failure. Finally, the findings of the research were analyzed using SPSS version 26 statistical software. Results: The mean age of patients was 3.66 ± 4.92 years. The number of deaths in the hyperuricemia group was significantly higher than in the normal uric acid group (P = 0.03); an odds ratio of 3.45 indicates that a high level of uric acid is a risk factor for death. In this study, the duration of hospitalization was longer in those who survived (P = 0.02). A particularly strong predictor in our analysis was the qSOFA score (P < 0.001), highlighting its critical role in determining outcome. Serum uric acid level and qSOFA scale showed no significant difference overall (P = 0.76); subgroup analysis among surviving and deceased patients between uric acid and the qSOFA scale presented the same result (P = 0.203 and P = 0.29, respectively). Conclusion: The level of uric acid can be considered a laboratory variable to predict the prognosis of patients.